Speech coding techniques and algorithms - A.Kassim, Liban; Khalifa, Othman Omran; Gunawan, Teddy Surya (IIUM Press, 2011)
Due to the growing need for bandwidth conservation and enhanced quality in wireless cellular and satellite communication, the research of low bit rate speech coder with acceptable quality is becoming increasingly important. Applications like Digital cellular and satellite telephony, video conferencing and internet voice communications, all have an increasing demand efficient use of bandwidth without compromising the quality